2016
DOI: 10.19082/3296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral and dental health on quality of life in Iranian preschool children and their families

Abstract: IntroductionOral and dental health is one of the most important factors that affect the quality of life of preschool children. This study determined the effect of oral and dental health of preschoolers on their quality of life and that of their parents.MethodsThis descriptive-cross sectional study asked 304 mothers of children aged 2–5 years from Babol, Iran, to complete an Early Childhood Oral Health Impact Scale (ECOHIS) questionnaire. Higher raw scores for ECOHIS indicate more oral problems and lower qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
2
9
0
4
Order By: Relevance
“…Also, similar to present study results, Nemati et al [ 22 ] found no significant difference in the effect of oral health on quality of life between boys and girls. The reason is that the children evaluated in this study were very young (preschool), and gender differences in these children may have not yet influenced their understanding of the aesthetic aspects of oral health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, similar to present study results, Nemati et al [ 22 ] found no significant difference in the effect of oral health on quality of life between boys and girls. The reason is that the children evaluated in this study were very young (preschool), and gender differences in these children may have not yet influenced their understanding of the aesthetic aspects of oral health.…”
Section: Discussionsupporting
confidence: 91%
“…Based on these findings, the children that participated in the present study had poorer dental health than the studies mentioned above. However, the recent study participants had better scores compared to the mean dmft index of Babol (4.39 ± 3.69) and Kerman (5.6 ± 3.6) preschool children [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…From its definition in 2007 to now, ECOHIS has been translated and validated in different countries to ensure an intercultural adaptation of the questionnaires but maintaining the same measuring method, which generally showed an acceptable degree of success [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] ( Table 1). However, it has not been widely applied yet in Italy, with the recent exception of Ferrazzano et al, who assessed changes in oral health-related quality of life and body growth in children aged 3-5 years following dental treatment under general anaesthesia due to severe dental caries.…”
Section: Validity Of Ecohis In Other Countriesmentioning
confidence: 99%
“…A lower level of schooling among parents/caregivers was associated with a greater impact on the OHRQoL of the preschoolers based on the parents/caregivers and children's self‐reports. Some studies have reported similar results, but they have only considered the reports of parents/caregivers using the ECOHIS . The habits of parents/caregivers and the family environment affect the health of children.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported similar results, but they have only considered the reports of parents/caregivers using the ECOHIS. 33,34 The habits of parents/caregivers and the family environment affect the health of children. A higher level of schooling is related to the search for greater care for one's children, which can minimize the consequences of oral problems due to greater access to dental services.…”
Section: Discussionmentioning
confidence: 99%